Transforming growth factor-β: an important mediator in Helicobacter pylori-associated pathogenesis - Shuang, Li N.; chuan, Xie; hua, Lu n. (Frontiers in Cellular and Infection Microbiology, 2015)
Helicobacter pylori (H. pylori) is a Gram-negative microaerophilic, curved bacillus that specifically colonizes the gastric mucosa. The interaction between virulence factors, host genetic factors and environmental factors contributes to the pathogenesis of H. pylori, such as atrophic gastritis and intestinal metaplasia. Infection with H. pylori has recently been recognized as the strongest risk factor for gastric cancer. As a pleiotropic cytokine, transforming growth factor (TGF)-β regulates various biological processes, ranging from cell cycle, cell proliferation, apoptosis, and metastasis. Recent studies have shed new light on the involvement of TGF-β signaling in the pathogenesis of H. pylori. This review focuses on the potential etiologic role of TGF-β in H. pylori-mediated gastric pathogenesis.